Indonesian Physical Fitness Test (TKJI) Conversion Assessment Application Program for Vocational School Students - Hidayat, Hidayat; Rohman, Ujang; Cholid, Abd. (Physical Education, Health and Recreation Study Program, Universitas Insan Budi Utomo, Indonesia, 2023)
This research aims to develop TKJI assessment software that is converted through the TKJI test application which is integrated via computer. The research method is research and development, namely developing the TKJI test assessment application through stages 1) analyzing product needs, 2) developing initial products, 3) carrying out expert validation, 4) carrying out trials, 5) revising the product, 6) product final research sample of class XII students taken randomly (ramdom). The results of the validation and testing of the TKJI application are; 1) in terms of the quality of the TKJI application, the material content quality is 97.11%, the media quality is 93.75 and the design quality is 98.61%. This shows that the TKJI test application is very feasible and suitable for use. Meanwhile, the student responses were 88.29% for the individual group, 88.75% for the small group and 83.18% for the large group with the very appropriate category. The results of this analysis can be concluded that the TKJI application is declared valid and very suitable for use as a medium for assessing the level of physical fitness for children aged 16 to 19 at the vocational school level.